Catalyst for catalyzing cracking of oleic acid to prepare low-carbon olefin as well as preparation method and application of catalyst

By mixing aluminum sources, metal sodium salts, pH adjusters, silicon sources and template agents in deionized water, and synthesizing a fractionated zeolites by using the hydrothermal one-pot method, the problems of short catalyst life of the hard template method and high cost of the soft template method are solved, and the catalyst life is extended and catalytic performance is improved.

CN119771481APending Publication Date: 2025-04-08BEIFANG UNIV OF NATITIES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510053183.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

In the prior art, there are defects in preparing the internal mesoporous channels of the catalyst by hard template method, which leads to a shortening of the catalyst life and a decrease in the cracking catalytic performance. At the same time, the cost of preparing the catalyst by soft template method is high and the process is complicated, which hinders the industrialization of the fractionated zeolites.

Method used

The aluminum source, metal sodium salt, pH adjuster, silicon source and template agent are used to fully mix in deionized water, and the fractionated zeolite is synthesized by a one-pot water heat method, which simplifies the preparation process and reduces the cost.

Benefits of technology

The prepared catalyst has excellent mesoporous channel structure, which extends the service life of the catalyst and significantly improves the catalytic performance of the production of low-carbon olefins by oleic acid cracking. The yield and oleic acid conversion of low-carbon olefins are higher than those of traditional CZSM-5 zeolites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771481A_ABST
    Figure CN119771481A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysts, and particularly relates to a catalyst for catalyzing cracking of oleic acid to prepare low-carbon olefin as well as a preparation method and application of the catalyst. During preparation, only an aluminum source, a metal sodium salt, a pH regulator, a silicon source and a template agent need to be added into deionized water to be fully mixed, then a simple hydrothermal one-pot method is adopted for synthesis, the synthesis method is easier, and the cost of used materials is lower. When the catalyst HMM-2 prepared by the experiment of the invention is used for catalytic cracking of oleic acid, the average value of the yield of low-carbon olefins is 57.2%, which is 17.4% higher than that of the traditional CZSM-5 zeolite, and the improvement rate is 43.7%; the conversion rate of oleic acid is 97.5% and is 6.7% higher than that of traditional zeolite, the improvement rate is 7.4%, and the cracking catalytic performance is excellent. After the continuous catalytic reaction for 36 hours, the yield of the low-carbon olefin is still higher than the yield of CZSM-5 after 12 hours, so that the catalyst disclosed by the invention is not easy to inactivate, and the service life is greatly prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysts, and in particular relates to a catalyst for catalyzing oleic acid cracking to produce light olefins, and a preparation method and application thereof. Background Art

[0002] Since China clearly put forward the "dual carbon" goal in 2020, my country's new energy has developed rapidly, while basic chemicals represented by olefins and aromatics are in short supply. Among them, low-carbon olefins (including ethylene, propylene and butene) are important basic chemical raw materials in the petrochemical industry, mainly used in the production of chemicals such as cosmetics, lubricants, rubber, plastics, detergents and polymers. However, the industrial production of low-carbon olefins is highly dependent on traditional fossil energy, such as naphtha cracking and coal conversion pathways, which will accelerate the consumption of traditional fossil energy. At the same time, the emission of large amounts of sulfur oxides and nitrogen oxides during the production process will not only pollute the environment and corrode equipment, but also endanger human health.

[0003] Biomass is the fourth largest energy source after coal, oil and natural gas, with abundant reserves, accounting for about 12% of the world's primary energy supply. Compared with the combustion of fossil fuels, biomass conversion produces much less nitrogen oxides, sulfur oxides and ash. Oleic acid, an 18-carbon carboxylic acid containing double bonds, can be more easily cracked to form light olefins. ZSM-5 molecular sieves are widely used in reaction processes such as petroleum refining, gas adsorption and ion exchange due to its advantages such as good thermal and chemical stability, special three-dimensional pore structure, adjustable active sites and a variety of different crystal phase structures.

[0004] For catalytic cracking of macromolecular reactants, the pore structure and acid properties of the catalyst not only affect the distribution of catalytic products, but also affect the diffusion and mass transfer of substances during the reaction. Therefore, the pore structure and acid properties of the catalyst are closely related to the selectivity and life of the catalyst. In current research, the introduction of mesoporous structures into traditional zeolites to prepare graded zeolites can effectively improve the diffusion and mass transfer of substances during the reaction. In existing research, the template method is usually used to prepare graded zeolites with special pore structures. However, the use of hard templates will cause cavities and discontinuous pores to form inside the catalyst. These defects will cause coke precursors to be retained inside the zeolite, reducing the catalyst life and affecting the cracking catalytic performance of the catalyst. Most soft templates are expensive and the manufacturing process is complicated, which hinders the industrial development of graded zeolites. In this context, it is of great significance to develop a graded zeolite with excellent mesoporous channels and low cost. Summary of the invention

[0005] Based on this, the present application provides a catalyst for catalytic cracking of oleic acid to produce low-carbon olefins, and its preparation method and application, in order to solve the technical problems in the prior art that the internal mesoporous channel defects of the catalyst prepared by the hard template method reduce the catalyst life and affect the cracking catalytic performance of the catalyst, and the soft template method has a high cost and a complicated production process for preparing the catalyst.

[0006] The technical solution of this application to solve the above technical problems is as follows:

[0007] A method for preparing a catalyst for catalytic cracking of oleic acid to produce light olefins comprises the following steps:

[0008] S10. Adding an aluminum source, a metal sodium salt and a pH adjuster to deionized water, stirring at room temperature until completely dissolved, to obtain a first mixed solution;

[0009] S20. Add a silicon source to the first mixed solution, stir thoroughly at room temperature until the silicon source is fully hydrolyzed, then add a template, stir until fully mixed, and obtain a second mixed solution;

[0010] S30. The second mixed solution is subjected to hydrothermal synthesis, and then washed and dried to obtain a solid powder;

[0011] S40. calcining the solid powder to obtain the catalyst for catalytic cracking of oleic acid to produce light olefins.

[0012] Preferably, in the above preparation method, the mass ratio of the aluminum source to the metal sodium salt is 1:(31.7 to 68.3).

[0013] Preferably, in the above preparation method, the metal sodium salt is a mixture of sodium sulfate and sodium chloride, and the mass ratio of the sodium sulfate to sodium chloride is (1.6 to 4.6):1.

[0014] Preferably, in the above preparation method, the aluminum source is selected from at least one of sodium aluminate, aluminum sulfate 18hydrate, aluminum isopropoxide, aluminum acetate, aluminum chloride, and aluminum nitrate nonahydrate.

[0015] Preferably, in the above preparation method, the pH value of the first mixed solution is 12 to 14.

[0016] Preferably, in the above preparation method, the mass ratio of the aluminum source, the silicon source and the template is 1:(100 to 150):(10 to 24).

[0017] Preferably, in the above preparation method, the silicon source is selected from tetraethyl orthosilicate, methyl silicate, ethyl silicate, propyl silicate, butyl silicate, 30wt% SiO 2 Aqueous solution, 40wt% SiO 2 At least one of the aqueous solutions.

[0018] Preferably, in the above preparation method, the template is cetylpyridinium bromide.

[0019] A catalyst for catalyzing the cracking of oleic acid to produce light olefins is prepared by using the above-mentioned preparation method.

[0020] The catalyst is used in the field of catalytic cracking of oleic acid to produce light olefins.

[0021] The above technical solution adopted in this application has at least the following advantages:

[0022] The present application discloses a method for preparing a catalyst for catalytic cracking of oleic acid to produce light olefins. It only requires adding an aluminum source, a metal sodium salt, a pH regulator, a silicon source and a template agent into deionized water, mixing them thoroughly, and then using a simple hydrothermal one-pot method to synthesize a graded zeolite (the catalyst of the present application). The synthesis method is easier, the cost of the materials used is lower, and the synthesis conditions are easier to control.

[0023] The present application discloses a catalyst for catalytic cracking of oleic acid to produce light olefins, which has excellent cracking catalytic performance. Experiments show that the catalyst HMM-2 sample prepared in the experimental example of the present application has an average light olefin yield of 57.2% in the catalytic cracking of oleic acid, which is 17.4% higher than that of traditional CZSM-5 zeolite, with an improvement rate of 43.7%; the oleic acid conversion rate is 97.5%, which is 6.7% higher than that of traditional zeolite, with an improvement rate of 7.4%.

[0024] At the same time, the catalyst HMM-2 sample has uniform mesoporous channels and a certain proportion of mesoporous pore volume. Because the hydrophobic group of the template used is connected to the hydrophilic group, the mesoporous channels formed by the template are connected to the microporous channels of MFI, which inhibits the formation of voids and discontinuous channels. The interconnected pore structure can reduce the mass transfer resistance of the raw material molecules, accelerate the transfer of cracking products, and inhibit the coke precursor from further forming stubborn coke, thereby extending the service life of the catalyst. Experiments show that after 36h of continuous catalytic reaction, the light olefin yield of the catalyst HMM-2 is still higher than the yield of CZSM-5 after 12h, indicating that the catalyst of the present application is less likely to deactivate and has a greatly extended service life. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is the XRD diagram of the catalyst HMM-1 obtained in the present invention.

[0026] Figure 2 It is the XRD diagram of the catalyst HMM-2 obtained in the present invention.

[0027] Figure 3 It is the XRD diagram of the catalyst HMM-3 obtained in the present invention.

[0028] Figure 4 It is the XRD diagram of the catalyst HMM-4 obtained in the present invention.

[0029] Figure 5 It is the XRD diagram of the catalyst HMM-5 obtained in the present invention.

[0030] Figure 6 It is the XRD diagram of the catalyst HMM-6 obtained in the present invention.

[0031] Figure 7 It is the XRD diagram of the catalyst HMM-7 obtained in the present invention.

[0032] Figure 8 It is the XRD diagram of the catalyst CZSM-5 obtained in the comparative example of the present invention.

[0033] Fig. 9 It is a SEM picture of the catalyst HMM-1 obtained in the present invention.

[0034] Fig.10 It is a SEM picture of the catalyst HMM-2 obtained in the present invention.

[0035] Fig.11 It is a SEM picture of the catalyst HMM-3 obtained in the present invention.

[0036] Fig.12 It is a SEM picture of the catalyst HMM-4 obtained in the present invention.

[0037] Fig.13 It is a SEM picture of the catalyst HMM-5 obtained in the present invention.

[0038] Fig.14 It is a SEM picture of the catalyst HMM-6 obtained in the present invention.

[0039] Fig.15 It is a SEM picture of the catalyst HMM-7 obtained in the present invention.

[0040] Fig.16 It is a SEM picture of the catalyst CZSM-5 obtained in the comparative example of the present invention.

[0041] Fig.17 It is the nitrogen absorption-desorption curve and pore size distribution diagram of the catalyst HMM-1 obtained by the present invention.

[0042] Fig.18 It is the nitrogen absorption-desorption curve and pore size distribution diagram of the catalyst HMM-2 obtained by the present invention.

[0043] Fig.19 It is the nitrogen absorption-desorption curve and pore size distribution diagram of the catalyst HMM-6 obtained by the present invention.

[0044] Fig. 20 It is the nitrogen absorption-desorption curve and pore size distribution diagram of the catalyst HMM-7 obtained by the present invention.

[0045] Fig.21 It is a nitrogen absorption-desorption curve and pore size distribution diagram of the catalyst CZSM-5 obtained in the comparative example of the present invention. DETAILED DESCRIPTION

[0046] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. The technical solution of the present invention will be further described below in conjunction with the drawings of the embodiments of the present invention, and the present invention is not limited to the following specific implementation methods.

[0047] In one specific embodiment of the present invention, a method for preparing a catalyst for catalytic cracking of oleic acid to produce light olefins (hereinafter referred to as catalyst) comprises the following steps:

[0048] S10. Adding an aluminum source, a metal sodium salt and a pH adjuster to deionized water, stirring at room temperature until completely dissolved, to obtain a first mixed solution;

[0049] Deionized water is used as a solvent in this scheme, and a pH regulator (sodium hydroxide, concentration ≥ 96%) is used to provide an alkaline environment for hydrothermal synthesis and silicon source hydrolysis. In the initial stage of hydrothermal synthesis, the aluminum source and the pH regulator are dissolved in deionized water and stirred at room temperature. Afterwards, a metal sodium salt is added to the mixture, which provides a portion of alkali metal ions, and continues to stir at room temperature. Further, the aluminum source in this application is selected from at least one of sodium aluminate, aluminum sulfate 18 hydrate, aluminum isopropoxide, aluminum acetate, aluminum chloride, and aluminum nitrate 9 hydrate, preferably sodium aluminate with a concentration of 99%; the pH regulator is preferably sodium hydroxide, with a concentration of ≥ 96%, and the main function of the pH regulator is to dissolve the aluminum source and the pH regulator in deionized water, adjust the pH between 12-14, and provide an alkaline environment for hydrothermal synthesis and silicon source hydrolysis. The mass ratio of the aluminum source to the metal sodium salt is 1: (31.7 to 68.3).

[0050] In a preferred embodiment, the metal sodium salt is a mixture of sodium sulfate and sodium chloride, and the mass ratio of the sodium sulfate to the sodium chloride is (1.6 to 4.6): 1

[0051] S20. Add a silicon source to the first mixed solution, stir thoroughly at room temperature until the silicon source is fully hydrolyzed, then add a template, stir until fully mixed, and obtain a second mixed solution; preferably, the silicon source is selected from tetraethyl orthosilicate, methyl silicate, ethyl silicate, propyl silicate, butyl silicate, 30wt% SiO 2 Aqueous solution, 40wt% SiO 2At least one of the aqueous solutions; the template is cetylpyridinium bromide (CET-Py, ≥96%), which is used to guide the formation of MFI topological structure and hierarchical channels. The amphiphilic template of cetylpyridinium bromide has both long-chain alkane hydrophobic groups and pyridine hydrophilic groups. By using this amphiphilic template, the surface tension of the aluminosilicate precursor in the initial gel can be changed, the hydrophilic group guides the formation of the MFI topological structure, and the hydrophobic group forms a hydrophobic layer to limit the growth of crystals and form nanocrystals. These nanocrystals form nanocrystal accumulations by rotating and overlapping. This hydrophobic layer will be removed in the subsequent calcination treatment and produce corresponding mesoporous channels; the hydrophobic groups of the amphiphilic template form hydrophobic layers on the surface of nanocrystals, which limit the continued growth of block crystals, and form a hydrophobic layer of fixed size through its strongly hydrophobic long-chain alkane groups. The catalyst sample prepared after calcination has uniform mesoporous channels and a certain proportion of mesoporous pore volume. Since the hydrophobic group of the template used is connected to the hydrophilic group, the mesoporous channels formed by the template are connected to the microporous channels of the MFI, which inhibits the formation of voids and discontinuous channels. The interconnected channel structure can reduce the mass transfer resistance of the raw material molecules, accelerate the transfer of cracking products, and inhibit the coke precursor from further forming stubborn coke. The mass ratio of the aluminum source, silicon source and template is 1: (100 to 150): (10 to 24).

[0052] S30. The second mixed solution is subjected to hydrothermal synthesis, and then washed and dried to obtain a solid powder;

[0053] S40. calcining the solid powder to obtain the catalyst for catalytic cracking of oleic acid to produce light olefins.

[0054] For example, the method for preparing a catalyst for catalytic cracking of oleic acid to produce light olefins is specifically as follows:

[0055] First, deionized water is used as a solvent, and a pH regulator is used to provide an alkaline environment for hydrothermal synthesis and hydrolysis of the silicon source. In the initial stage of hydrothermal synthesis, the aluminum source and the pH regulator are dissolved in deionized water and stirred at room temperature. Then, a metal sodium salt is added to the deionized water mixture in which the aluminum source and the pH regulator are mixed, and stirring is continued at room temperature to obtain a first mixed solution.

[0056] Next, when the crystal particles in the first mixed solution completely disappear, add a silicon source, which provides a silicon source and part of an alcohol solvent for the zeolite framework after hydrolysis in an alkaline environment, and stir well at room temperature to fully hydrolyze the silicon source. After the above hydrolysis process is completed, add a template to obtain a second mixed solution.

[0057] After all substances in the second mixed solution are completely mixed, they are transferred to a polytetrafluoroethylene liner and hydrothermally synthesized in a homogeneous reactor at a synthesis temperature of 120°C to 180°C for 4 to 5 days. After the hydrothermal synthesis is completed, the hydrothermal synthesis product is washed with deionized water to remove excess inorganic salts, and then dried in an oven at 90°C to 110°C for 10 to 15 hours to remove moisture to obtain a solid powder.

[0058] Finally, the dried solid powder is calcined at 500°C to 700°C for 3h to 7h, preferably at 600°C for 5h in an air atmosphere to remove the organic template to obtain a white powder, which is the catalyst sample of the present invention for catalytic cracking of oleic acid to produce light olefins (named HMM series samples).

[0059] In another specific embodiment of the present invention, a catalyst for catalytic cracking of oleic acid to produce light olefins is prepared using the above-mentioned preparation method.

[0060] It is worth noting that the process temperature and process time involved in the above-mentioned embodiments are all temperatures or times used in the experimental process. Those skilled in the art can make reasonable adjustments within the error range based on the process temperature and process time provided by the present invention, which should be included in the protection scope of the present invention.

[0061] The technical solution and technical effects of the present invention are further illustrated below through specific experimental examples.

[0062] 1. Experimental Materials

[0063] In the examples of the present invention, oleic acid was from Aladdin (Shanghai, China) with the specification of analytical grade AR; other reagents and solvents were commercially available and could be used without further purification.

[0064] 2. Experimental equipment

[0065] A fixed-bed reactor was used as the catalytic reactor, and the light olefin products were detected online using a GC-7920 gas chromatograph (Tengzhou, Shandong, China) equipped with a HPAl / KCl capillary column (30 m × 0.530 mm × 15 μm, produced by Agilent Technologies, USA), a flame ionization detector (FID), and a thermal conductivity detector (TCD).

[0066] 3. Comparative ratio

[0067] A conventional ZSM-5 zeolite having a coffin-shaped structure synthesized from tetrapropylammonium hydroxide was used as a catalyst for comparative experiments, that is, a catalyst used in the prior art for the cracking of oleic acid to produce light olefins. The same silicon source and aluminum source as those of the catalyst in the embodiment of the present application were used, and the silicon-aluminum ratio in the initial gel was ensured to be the same. The specific synthesis process is as follows:

[0068] Using deionized water as solvent, 8.4g of tetrapropylammonium hydroxide (25% aqueous solution) was mixed with 20g of deionized water and stirred continuously at room temperature for 1h. After that, 0.205g of sodium aluminate (99%) and 0.52g of sodium hydroxide (≥96%) were added, and stirring continued at room temperature for 1h. After the crystal particles in the solution were completely dissolved, 20.8g of tetraethyl orthosilicate (TEOS, 98%) was slowly added to the solution, and then the initial gel was obtained after continuous stirring at room temperature for 16h. After that, the gel was transferred to a hydrothermal reactor with a crystallization temperature of 170℃ and a crystallization time of 72h. After the hydrothermal synthesis was completed, the sample was cooled to room temperature and the crystalline solid was washed 3 to 4 times with deionized water, and the obtained solid product was dried at 120℃ for 12h. The dried sample was calcined in an air atmosphere for 6h to remove the organic template, and the white solid obtained was the traditional ZSM-5 zeolite (CZSM-5). The X-ray diffraction spectrum, scanning electron microscopy and nitrogen adsorption-desorption results of the sample are shown in Figure 8 , Fig.16 and Fig.21 Shown

[0069] 4. Embodiment 1

[0070] Dissolve 0.2g sodium hydroxide (≥96%) and 0.041g sodium aluminate (99%) in 14.4g deionized water, adjust the pH between 12 and 14, and stir at room temperature for 0.5h. Then, add 1.5g sodium sulfate (≥99%) and 0.5g sodium chloride (≥99%) to the mixture, and continue to stir at room temperature for 0.5h. When the crystalline particles in the above solution completely disappear, add 5g tetraethyl orthosilicate (TEOS, 98%) to the solution, and continue to stir at room temperature for 4h. Then, add 0.95g hexadecylpyridinium bromide (CET-Py, ≥96%) to the mixture, the amount added is shown in Table 1, and continue to stir at room temperature for 2h. Then, transfer the mixture to a 100mL polytetrafluoroethylene liner and perform hydrothermal synthesis in an oven. The hydrothermal synthesis temperature is 150℃ and the hydrothermal time is 4 days. After the hydrothermal synthesis, the solid powder was washed with deionized water to remove the alkali in the sample, and the washed powder was dried at 100° C. for 12 h. Thereafter, the solid was calcined at 600° C. for 5 h to obtain a white powder as the samples of the present invention (named HMM-1 to HMM-3).

[0071] Table 1 Example 1 Cetylpyridinium bromide content in a sample

[0072] Cetylpyridinium bromide (g) HMM-1 0.43 HMM-2 0.95 HMM-3 1.35

[0073] The X-ray diffraction spectrum of the HMM-1 sample is as follows Figure 1As shown in Figure 1, the HMM-1 sample shows MFI characteristic diffraction peaks. Fig. 9 As shown in Figure 2, the HMM-1 sample has a crystal stacking structure. The nitrogen adsorption-desorption results are shown in Figure 2. Fig.17 As shown on the left, the image shows a clear hysteresis loop, indicating the existence of a mesoporous structure. The pore size distribution of the corresponding sample is shown in Fig.17 As shown on the right, the image shows a clear characteristic peak between 2-5 nm, indicating that the HMM-1 sample has a clear pore size distribution between 2-5 nm.

[0074] The X-ray diffraction spectrum of the HMM-2 sample is as follows Figure 2 As shown in Figure 2, the HMM-2 sample shows MFI characteristic diffraction peaks. Fig.10 As shown in Figure 2, the HMM-1 sample has a crystal stacking structure. The nitrogen adsorption-desorption results are shown in Figure 2. Fig.18 As shown on the left, the image shows a clear hysteresis loop, indicating the existence of a mesoporous structure. The pore size distribution of the corresponding sample is shown in Fig.18 As shown on the right, the image shows a clear characteristic peak between 2-5 nm, indicating that the HMM-1 sample has a clear pore size distribution between 2-5 nm.

[0075] The X-ray diffraction spectrum and scanning electron microscope image of HMM-3 sample are shown as follows: Figure 3 and Fig.11 The X-ray diffraction spectrum of the sample is shown in Figure 3 As shown in Figure 2, the HMM-3 sample does not show the MFI characteristic diffraction peak, proving that no crystal structure has been formed. Fig.11 As shown, the HMM-3 sample exhibits spherical accumulation.

[0076] The catalysts obtained in the above embodiments and comparative examples were evaluated for their catalytic performance in the cracking of oleic acid to produce low-carbon olefins. The specific reaction conditions are as follows: 0.5 g of the above-obtained catalyst was weighed, and the catalyst sample was wrapped with 1-3 μm quartz wool (XH-SYM) and placed in a fixed bed reactor. Before the reaction started, high-purity nitrogen (99.999%) was used to purge the fixed bed reaction pipeline to evacuate the air in the pipeline. Then, the reactor temperature was raised to 500°C using a heating jacket at a heating rate of 8°C / min. When the reactor temperature was raised to the reaction temperature, a plunger pump was used to add the raw oleic acid to the reactor at a flow rate of 0.03 mL / min. After the reaction started, the product molecules were detected using an online chromatogram every 1 h, and the yield of low-carbon olefins was calculated. The conversion rate of oleic acid was calculated by detecting the liquid phase product of methyl esterification to obtain the mass percentage of unconverted oleic acid in the liquid phase product, and the conversion rate of oleic acid was obtained by subtracting the percentage from 100%. The yield of light olefins and the conversion rate of oleic acid obtained by catalyst cracking oleic acid are shown in the following table:

[0077] Table 2 Test results of cracking oleic acid reaction of catalysts obtained in Example 1 and Comparative Example

[0078] catalyst Reaction time (h) Average light olefin yield (%) Light olefin yield (%) Oleic acid conversion rate (%) HMM-1 12h 49.5 51.4-47.6 96 HMM-2 12h 57.2 59.9-55.2 97.5 CZSM-5 12h 39.8 42.2-38.6 90.8

[0079] Since the HMM-3 sample showed spherical accumulation and its appearance was unqualified, it was not tested for cracking oleic acid reaction. As can be seen from the above table, the catalyst samples HMM-1 and HMM-2 have higher yields of low-carbon olefins and oleic acid conversion rates than the zeolite CZSM-5 in the prior art in the cracking of oleic acid to produce low-carbon olefins, especially the catalyst HMM-2, with an average yield of 57.2% of low-carbon olefins, which is 17.4% higher than the traditional CZSM-5 zeolite, and the increase rate is 43.7%; the oleic acid conversion rate is 97.5%, which is 6.7% higher than the traditional zeolite, and the increase rate is 7.4%, and the cracking catalytic performance is excellent.

[0080] 5. Embodiment 2

[0081] The method for preparing the catalyst of sample HMM-2 in Example 1 was repeated, and the amount of metal sodium salt added was changed (see Table 3). The other steps were the same as in Example 1, and the obtained samples were HMM-4 to HMM-7.

[0082] Table 3: Content of metal sodium salt in each sample of Example 2

[0083] Sodium sulfate(g) Sodium chloride (g) HMM-4 0 0.5 HMM-5 1.5 0 HMM-6 0.8 0.5 HMM-7 2.3 0.5

[0084] The X-ray diffraction spectrum of the HMM-4 sample is as follows Figure 4 As shown in the figure, the HMM-4 sample shows MFI characteristic diffraction peaks, but the characteristic diffraction peak intensity is low and an obvious base peak appears. Fig.12 As shown, the HMM-4 sample formed bulk crystals with a fusiform structure, and these crystals did not form a close crystal packing.

[0085] The X-ray diffraction spectrum of the HMM-5 sample is as follows Figure 5 As shown in Figure 2, the HMM-5 sample shows MFI characteristic diffraction peaks. Fig.13 As shown, the HMM-6 sample formed traditional coffin plate-shaped crystals, and these crystals did not form a close crystal packing.

[0086] The X-ray diffraction spectrum of the HMM-6 sample is as follows Figure 6 As shown in Figure 2, the HMM-6 sample shows MFI characteristic diffraction peaks. Fig.14 As shown in Figure 2, the HMM-1 sample has a crystal stacking structure. The nitrogen adsorption-desorption results are shown in Figure 2. Fig.19 As shown on the left, the image shows a clear hysteresis loop, indicating the existence of a mesoporous structure. The pore size distribution of the corresponding sample is shown in Fig.19As shown on the right, the image shows an obvious characteristic peak between 2-5 nm, indicating that the HMM-3 sample has an obvious pore size distribution between 2-5 nm.

[0087] The X-ray diffraction spectrum of the HMM-7 sample is as follows Figure 7 As shown in Figure 2, the HMM-7 sample shows MFI characteristic diffraction peaks. Fig.15 As shown in Figure 2, the HMM-4 sample has a crystal stacking structure. The nitrogen adsorption-desorption results are shown in Figure 2. Fig. 20 As shown on the left, the image shows a clear hysteresis loop, indicating the existence of a mesoporous structure. The pore size distribution of the corresponding sample is shown in Fig. 20 As shown on the right, the image shows an obvious characteristic peak between 2-5 nm, indicating that the HMM-7 sample has an obvious pore size distribution between 2-5 nm.

[0088] The catalytic performance of the catalyst in the above example for cracking oleic acid to produce light olefins was evaluated. The specific reaction conditions were the same as above. The light olefin yield and oleic acid conversion rate obtained by cracking oleic acid with the catalyst are shown in the following table:

[0089] Table 4 Test results of cracking oleic acid reaction of the catalyst obtained in Example 2

[0090]

[0091] As can be seen from the table above, when only sodium sulfate or sodium chloride is added to the metal sodium salt, the catalyst crystals do not form a dense crystal stack and the appearance is unqualified. When the mass ratio of sodium sulfate to sodium chloride is 1.6:1 (HMM-6) and 1.6:1 (HMM-7), the average light olefin yield of the catalyst is about 50%, and the oleic acid conversion rate is above 94%, both higher than traditional zeolites, but lower than HMM-2, indicating that when other raw materials remain unchanged and the mass ratio of sodium sulfate to sodium chloride is 3:1, the prepared catalyst has the best cracking catalytic performance.

[0092] 5. Embodiment 3

[0093] The above catalyst HMM-2 was used to evaluate the catalytic performance of oleic acid cracking to produce light olefins. The specific reaction conditions were the same as above. After 36 hours of reaction, the light olefin yield was calculated. The data are as follows:

[0094] Table 5 Catalyst cracking oleic acid reaction test results

[0095] catalyst Reaction time (h) Average light olefin yield (%) Light olefin yield (%) HMM-2 36h 50.9 59.9-38.7

[0096] It can be seen from the above table that after 36 hours of continuous catalytic reaction, the yield of light olefins of the catalyst HMM-2 prepared by the present invention is still higher than that of CZSM-5 after 12 hours, which proves that the additional mesoporous structure in HMM-2 improves the deposition of coke and makes HMM-2 less prone to deactivation.

[0097] In summary, it is shown that the catalyst provided by the present invention can improve the catalytic performance of the catalyst for preparing light olefins by cracking oleic acid. The catalyst of the present invention has excellent cracking catalytic performance and long service life, and the raw materials involved in the catalyst in the present invention are easy to obtain directly, which greatly simplifies the preparation process of the catalyst.

[0098] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst for catalytic cracking of oleic acid to produce light olefins, characterized in that: The following steps are involved: S10. Adding an aluminum source, a metal sodium salt and a pH adjuster to deionized water, stirring at room temperature until completely dissolved, to obtain a first mixed solution; S20. Add a silicon source to the first mixed solution, stir thoroughly at room temperature until the silicon source is fully hydrolyzed, then add a template, stir until fully mixed, and obtain a second mixed solution; S30. The second mixed solution is subjected to hydrothermal synthesis, and then washed and dried to obtain a solid powder; S40. calcining the solid powder to obtain the catalyst for catalytic cracking of oleic acid to produce light olefins.

2. The preparation method according to claim 1, characterized in that: The mass ratio of the aluminum source to the metal sodium salt is 1:(31.7 to 68.3).

3. The preparation method according to claim 1, characterized in that: The metallic sodium salt is a mixture of sodium sulfate and sodium chloride, and the mass ratio of the sodium sulfate to the sodium chloride is (1.6 to 4.6):

1.

4. The preparation method according to claim 1, characterized in that: The aluminum source is selected from at least one of sodium aluminate, aluminum sulfate 18-hydrate, aluminum isopropoxide, aluminum acetate, aluminum chloride, and aluminum nitrate nonahydrate.

5. The preparation method according to claim 1, characterized in that: The pH value of the first mixed solution is 12 to 14.

6. The preparation method according to claim 1, characterized in that: The mass ratio of the aluminum source, the silicon source and the template is 1:(100 to 150):(10 to 24).

7. The preparation method according to claim 1, characterized in that: The silicon source is selected from at least one of tetraethyl orthosilicate, methyl silicate, ethyl silicate, propyl silicate, butyl silicate, 30 wt % SiO2 aqueous solution, and 40 wt % SiO2 aqueous solution.

8. The preparation method according to claim 1, characterized in that: The template agent is cetylpyridinium bromide.

9. A catalyst for catalytic cracking of oleic acid to produce light olefins prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the catalyst according to claim 9 in the field of catalytic cracking of oleic acid to produce light olefins.